Understanding public perspectives on genetically engineered Brinjal and the adoption of modern biotechnology in Bangladesh - Ahmed, Sium; Shohael, Abdullah Mohammad; Ahamed, Tanvir; Ahmed, Razu; Ahmed, Shawon; Hassan, H. M. Shahid (Frontiers in Bioengineering and Biotechnology, 2024)
The agricultural sector in Bangladesh is currently facing numerous challenges. The country is currently endeavoring to adopt modern biotechnological tools, such as genetic engineering, to modify crops with the aim of ensuring food security. Notably, Bt Brinjal represents a significant milestone as the first genetically engineered (GE) food crop commercially cultivated in South Asia. Public perception and awareness are crucial steps forward for accepting and commercializing GE crops within society. The study discussed here aims to assess public perception and awareness regarding modern biotechnology and GE crops, focusing mainly on Bt Brinjal in Bangladesh. A random survey considered demographic factors such as age, gender, hometown, educational qualification, and occupation to explore the public attitudes towards Bt Brinjal and modern biotechnology. Approximately one-third of those surveyed considered Bt Brinjal safe for consumption, and a third expressed a willingness to buy Bt Brinjal, while nearly two-thirds believed it would gain popularity in the market alongside other crops. Most respondents recognized the necessity of utilizing modern biotechnology for crop improvement beyond Bt Brinjal, and respondents with science backgrounds displayed higher awareness and a more positive attitude than those with limited education or non-science backgrounds. This study explores the public perceptions of Bt Brinjal and the adoption of modern biotechnology in Bangladesh by examining factors such as knowledge dissemination, acceptance levels, and concerns related to GE crops, and offers a meaningful perspective that can shape decision-making processes to promote agricultural sustainability and achieve relevant sustainable development goals in Bangladesh.